A preliminary attempt to investigate mirror self-recognition in Octopus vulgaris - Amodio, Piero; Fiorito, Graziano (Frontiers in Physiology, 2022)
Mirror self-recognition (MSR) is a potential indicator of self-awareness. This capability has been widely investigated among vertebrates, yet it remains largely unstudied in invertebrates. Here we report preliminary data about behavioural responses exhibited by common octopuses (Octopus vulgaris) toward reflected images of themselves and explore a procedure for marking octopus’ skin in order to conduct the Mark test. Octopuses (N=8) received four familiarization trials with a mirror and four familiarization trials with a control stimulus: a non-reflective panel (Panel group, N=4) or the sight of a conspecific housed in an adjacent tank (Social group, N=4). Subsequently, octopuses were marked with non-toxic nail polish in the area where the Frontal White Spots are expressed, and they received one test trial with the mirror and one control trial with no mirror. We found that octopuses in the Panel group tended to exhibit a stronger exploratory response toward the mirror than the non-reflective panel, but performed agonistic responses only in the presence of the mirror. In contrast, octopuses in the Social group exhibited comparable exploratory and agonistic behaviours toward the mirror and the sight of the conspecific. In the Mark test, octopuses frequently explored the mark via their arms. However, mark-directed behaviours were also observed in the absence of the mirror and in sham-marked individuals, thus suggesting that proprioceptive stimuli drove these responses. Despite the limitations associated with our marking procedure, the baseline data collected in this pilot study may facilitate the further testing of MSR in the octopus and other cephalopods.